Volumetry and Surgical Grading Systems for Vestibular Schwannoma Size Assessment and their Relationship to Postoperative Facial Nerve Function - Strauß, Catharina; Rampp, Stefan; Scheller, Christian; Prell, Julian; Strauss, Christian; Dörfler, Arnd; Engelhorn, Tobias (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Aims Treatment modalities in vestibular schwannoma (VS) are difficult to compare since different techniques for size measurements are used. The purpose of this study was to evaluate the relation between different tumor size grading systems regarding their compatibility as well as the relationship to facial nerve outcome facilitating comparisons of different studies.
CRIS-Team WoS Importer:2021-06-18